2015
DOI: 10.1021/acs.jafc.5b00923
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antibodies and Development of an Indirect Competitive Immunoassay for Detection of Deamidated Gluten

Abstract: Diversification of gluten applications in the food and cosmetics industries was achieved through the production of water-soluble gluten that can be obtained by deamidation. Current analytical methods dedicated to gluten detection failed to detect deamidated gluten. After immunizing mice with the peptide LQPEEPFPE conjugated to keyhole limpet hemocyanin, five mouse monoclonal antibodies (mAbs) were produced and sequences of bound epitopes were determined as XPXEPFPE, where X is Q or E. The mAbs exhibited high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 30 publications
0
27
0
1
Order By: Relevance
“…The equivalent triggering activity of the IgE pool with that of the monoclonal chI-gE-DG1 suggests that a limited IgE repertoire might be involved in allergy to acid-HWPs, with IgE preferentially binding highly deamidated sequences. However, we observed that the patients' sera displayed a somewhat larger reactivity than the chIgE-DG1, notably towards low deamidated products or epitopes [11,13]. Chemical deamidation is a random process.…”
Section: Discussionmentioning
confidence: 71%
“…The equivalent triggering activity of the IgE pool with that of the monoclonal chI-gE-DG1 suggests that a limited IgE repertoire might be involved in allergy to acid-HWPs, with IgE preferentially binding highly deamidated sequences. However, we observed that the patients' sera displayed a somewhat larger reactivity than the chIgE-DG1, notably towards low deamidated products or epitopes [11,13]. Chemical deamidation is a random process.…”
Section: Discussionmentioning
confidence: 71%
“…Gliadins and glutenins, the main components of wheat proteins, are characterized by homologous domains constituted of repeated sequences of 6-8 amino acids rich in glutamines. During acid-hydrolysis, the random process of deamidation results in heterogeneous deamidation in each repeated sequences [3]. This work investigated the effect of the deamidation rates of the repeated sequences of a-HWP on their triggering potency.…”
Section: Discussionmentioning
confidence: 99%
“…Mariona Pascal 1 , Olga Dominguez 2 , Rosa Maria Jiménez-Feijoo 2 , Thorsten Graf 3 , Tanja Scheuermann 3 , Dominique Revets 3 , Clara San Bartolomé 1 , Jaime Lozano 2 , Monica Piquer 2 , Montserrat Alvaro 2 , Adrianna Machinena 2 , Maria Teresa Giner 2 , Markus Ollert 3 , Ana Maria Plaza-Martin 2 , Annette Kuehn 3 1 Immunology Department, CDB, Hospital Clinic, Barcelona, Spain; 2 Allergy and Clinical Immunology Department, Hospital Sant Joan de Déu, Esplugues De Llobregat, Spain; 3 Department of Infection and Immunity, Luxembourg Institute of Health, Esch-Sur-Alzette, Luxembourg Correspondence: Mariona Pascal -mpascal@clinic.ub.es Clinical & Translational Allergy (CTA) 2018, 8(Suppl 1):P48 Background: Fish is not only an important component in the Mediterranean diet, it is also a common elicitor of food-allergic reactions. The clinical work-up includes anamnesis, sera and skin reactivity analysis and, in some patients, oral provocations.…”
Section: P47mentioning
confidence: 99%
“…The competitive inhibition capacities of the synthesized peptides were measured by a competitive ELISA as described 15) with a little revision. High-binding ELISA plates were coated with 50 μL of 2 μg/mL Gly m Bd 28K protein which we had extracted previously from soybean, followed by blocking with 5% nonfat dry milk.…”
Section: Competitive Inhibition Elisamentioning
confidence: 99%